Effectiveness of Cheap Market Operation Policy in Bandung City - Restu Widyo Sasongko (Journal of Governance, 2024)
The government is very interested in maintaining price stability and the availability of food, especially rice, which is the staple food for almost all of Indonesia's population. One of the efforts made is to organize a cheap SPHP medium rice market operation with the hope that people, especially those with low purchasing power, can meet their needs. This study examines the effectiveness of cheap market operations organized by the Bandung City Government in situations of rice price spikes. The study was conducted using qualitative methods and took cases from three sub-districts. Data was collected through interview techniques, observation, and documentation, and then analysed using an interactive model. The results of the study show that cheap market operations are not an effective strategy to overcome the spike in rice commodity prices. After the implementation of the low-cost operation, the price of rice on the market continues to exceed the highest retail price (HET), and it is difficult for people to obtain rice at an affordable price. To overcome fluctuations in rice prices in the market, implementing market operations is considered more appropriate, and through this policy, the government intervenes in the market with rice from government food reserves managed by Perum BULOG. Apart from ensuring the availability of rice, market intervention can stabilize prices more quickly, have a longer impact, and cover a wider area.